Design, synthesis and biological evaluation of a series of iron and copper chelating deferiprone derivatives as new agents active against Candida albicans. (15th June 2021) - Bortolami, Martina; Pandolfi, Fabiana; Messore, Antonella; Rocco, Daniele; Feroci, Marta; Di Santo, Roberto; De Vita, Daniela; Costi, Roberta; Cascarino, Paola; Simonetti, Giovanna; Scipione, Luigi
Graphical abstract: Abstract: Candida albicans, in specific conditions, is responsible of severe invasive systemic candidiasis that are related to its ability to produce biofilm on biological and artificial surfaces. Many studies reported the role of iron in fungal growth and virulence and the ability of metal chelating agents to interfere with C. albicans metabolism, virulence and biofilm formation. Here we report the activity of 3-hydroxy-1, 2-dimethyl-4(1 H )-pyridinone (deferiprone) derivatives against C. albicans planktonic cells and biofilm. Some of the studied compounds (2b and 3b ) were able to chelate Fe(III) and Cu(II), and showed an interesting activity on planktonic cells (MIC50 of 32 μg/mL and 16 μg/mL respectively) and on biofilm formation (BMIC50 of 32 μg/mL and 16 μg/mL respectively) in cultured ATCC 10, 231 C. albicans ; this activity was reduced, in a concentration dependent way, by the addition of Fe(III) and Cu(II) to the culture media. Furthermore, the most active compound 3b showed a low toxicity on Galleria mellonella larvae.